2020
DOI: 10.3390/polym12030620
|View full text |Cite
|
Sign up to set email alerts
|

Polymer- and Hybrid-Based Biomaterials for Interstitial, Connective, Vascular, Nerve, Visceral and Musculoskeletal Tissue Engineering

Abstract: In this review, materials based on polymers and hybrids possessing both organic and inorganic contents for repairing or facilitating cell growth in tissue engineering are discussed. Pure polymer based biomaterials are predominantly used to target soft tissues. Stipulated by possibilities of tuning the composition and concentration of their inorganic content, hybrid materials allow to mimic properties of various types of harder tissues. That leads to the concept of "one-matches-all" referring to materials posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 265 publications
(309 reference statements)
0
41
0
Order By: Relevance
“…MMP9 was recently found to play an important role in keratinocyte migration and is expressed at the edge of migrating keratinocytes. On the other hand, decorin is a small leucine-rich proteoglycan that is found in the ECM and is known to regulate remodeling of the ECM, thus leading to scar formation and skin tissue regeneration [ 50 ]. Taken together, these results showed that the addition of CS extract may regulate cellular proliferation and ECM remodeling, therefore leading to enhanced skin tissue regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…MMP9 was recently found to play an important role in keratinocyte migration and is expressed at the edge of migrating keratinocytes. On the other hand, decorin is a small leucine-rich proteoglycan that is found in the ECM and is known to regulate remodeling of the ECM, thus leading to scar formation and skin tissue regeneration [ 50 ]. Taken together, these results showed that the addition of CS extract may regulate cellular proliferation and ECM remodeling, therefore leading to enhanced skin tissue regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the degradation mechanism, fibrinolysis may be the key player in the temporal and spatial arrangement to promote bone tissue regeneration and tissue infiltration into defects [ 96 , 97 , 98 ]. Therefore, controllable biodegradability and biological compatibility have practical potential for both 3D scaffolds and the characterization biopolymers for drug delivery systems with additional biologics, such as cells, enzymes, and growth factors, in order to promote hard tissue regeneration [ 99 , 100 , 101 ]. As a result of their relatively poor mechanical properties, and despite their excellent biological potential, composite biomaterials like fibrin-synthetic polymer materials or fibrin-inorganic materials have been recently developed for use in 3D architectures and have been investigated to improve their biomechanical strength for musculoskeletal and dental tissue engineering [ 102 , 103 ].…”
Section: Natural Biopolymers For Periodontal Hard Tissue Regeneratmentioning
confidence: 99%
“…Hydrogel surface functionalization or bioprinting provides a special biocoating that could serve as a 2D or 3D template for cell adhesion [7], align cells [8], or encapsulate and release functional biomolecules like alkaline phosphatase [9]. Various polymers can be used to construct hydrogels for tissue engineering [10]. However, a more interesting approach is using polymers with ionic cross-linkage mechanisms, like alginate and gellan gum, due to easy control of gelation and a chemically "mild" method of gel preparation.…”
Section: Introductionmentioning
confidence: 99%